Attitudes toward Homosexuality among Catholic-Educated University Graduates - Callegher, Jonathan D. (Catholic Education: A Journal of Inquiry and Practice, 2010)
Depending on the area of academic concentration, formal education beyond the secondary school level may present Catholic-educated individuals with a steady stream of perspectives, theories, and worldviews on a variety of sociocultural issues, including sexuality, that are different from those of the Catholic Church. Increasingly, liberal attitudes of young Catholics toward gay and lesbian issues may reflect a Catholic cohort that views moral questions as increasingly ambiguous and more open to personal interpretation. The purpose of this study is to uncover the themes related to how the completion of a university social science program and corresponding exposure to perspectives that are different from those of the Catholic Church has influenced Catholic-educated individuals’ attitudes toward homosexuality. The attitudes of 12 young adults who have graduated from a Catholic secondary school and have subsequently graduated from a social science program at a nonreligious, liberal university are herein explored.